活性イオウによるパターン認識受容体と環境ストレス応答の制御機構 - 澤, 智裕 (日本薬理学会年会要旨集, 2021)
Pattern recognition receptors (PRRs) play an important role in elimination of pathogenic microbes as well as damaged tissue debris by activating innate inflammatory responses. Membrane-bound PRR Toll-like receptors (TLRs) produces inflammatory cytokines such as tumor necrosis factor alpha (TNFalpha) as well as type I interferons. Cysteine persulfide (CysSSH) and polysulfides (CysS[S]nH, n > 2) are cysteine derivatives having sulfane sulfur atoms bound to cysteine thiol. Cysteine persulfide exist as a component of glutathione (GSH) as GSH persulfide (GSSH) and as protein-bound persulfide. Those cysteine persulfides act as reactive sulfur species because of their high chemical properties like antioxidative and nucleophilic activities. We found that reactive sulfur species contribute to the negative regulation of TLR signaling via inhibition of NF-kappaB pathway (Cell Chem Biol, 2019). We also found recently that reactive sulfur species down regulate inflammasome signaling (unpublished data). In this seminar, regulation of PRR signaling by reactive sulfur species will be discussed.